Peningkatan Proses Dan Hasil Belajar IPAS Menggunakan Model Pembelajaran Think Pair Share (TPS) Pada Siswa Kelas IV Di SDN 29/II Sungai Mancur - Shinta Selina Nugrah; Megawati Megawati; Opi Andriani (Master of Pedagogy and Elementary School Learning, 2026)
Based on preliminary observations, classroom action research was conducted on fourth-grade students at SDN 29/II Sungai Mancur. The findings indicate that students' scientific learning outcomes are low, as seen by their cognitive learning successes falling short of the school's KKTP of 70.  Whereas students who have been reported to have finished have a percentage of 41.7% in science learning outcomes, those who have not completed have a proportion of 58.3%.  “Thus, the Think Pair Share (TPS) learning approach is the one that can enhance student learning outcomes.  The aim of this study was to ascertain how the Think Pair Share (TPS) Learning model may be applied to enhance the science learning process and outcomes in every cycle.  Classroom Action Research (CAR) is the research methodology employed.  The study was carried out in two cycles, with planning, action implementation, observation, and reflection included in each cycle.  Twelve fourth-grade children from SDN 29/II Sungai Mancur served as the research subjects.  Both qualitative and quantitative data were collected for this investigation”.  qualitative information in the form of student and teacher observation forms.  The proportion of teacher performance observation sheets, the percentage of student learning process observation sheets, and the % of student science learning outcome assessments using the Think Pair Share (TPS) learning model are the sources of quantitative data.  This study's findings include: 1) a 98.9% rating for “the Teacher Performance Process in science learning using the Think Pair Share (TPS) learning model, 2) a 79.1% rating for the Student Learning Process in science learning using the Think Pair Share (TPS) learning model, and 3) an increase in student learning outcomes in cycles I and II”.  Cycle II had a 16.6% increase in the score, with 83.3% of the total falling into the "Very Good" category, up from cycle I's 66.7% "Enough" category.  Applying the Think Pair Share (TPS) learning model can enhance the learning process for students and raise learning outcomes by assisting them in solving difficulties through discussion.